Sustainable Cultural and Natural Heritage Tourism: A Lever for Urban Sustainability of Sreemangal - Islam, Mohammed Saiful (Journal of Bangladesh Institute of Planners, 2019)
Cultural and natural heritage tourism is a means of economic development that achieves economic escalation through attracting visitors from outside of a host community. This paper illustrates that the tourism sector while bringing economic benefits, hitherto many cities like Sreemangal has been experiencing the negative impacts of uncontrolled conventional tourism. Therefore, the evaluation of the present study reveals requirements for well designed plans of sustainable cultural and natural heritage tourism to ensure urban sustainability of Sreemangal. The study is mainly exploratory in nature and based on secondary data and information, although some information has been collected from primary sources as well. The paper explores that sustainable tourism development is more appropriate, because it is deliberated, controlled and long term development that generates jobs, overseas exchange earnings, new infrastructure whilst safeguarding cultural and natural heritage, and living culture, as well as minimizing negative environmental and social impacts of the city. Hence most essential components which recognize for the sustainable cultural and natural heritage based tourism development in Sreemangal are environmental protection, reduction of climate change impacts, resource efficiency and sustainable economic growth, social inclusiveness and poverty reduction, cultural values, diversity and natural heritage conservation, coordination of stakeholders, and effectual governance with tools and policies. JBIP, Vol. 12, 2019 (Printed in June 2020), pp. 81-96